Implantação do Programa Minha Casa Minha Vida nos municípios de Crato, Juazeiro do Norte e Barbalha: arranjos institucionais e condições de inserção urbana - Pessoa, Thamires Machado (2016)
In the last years the heating of the real estate market in the national level has been observed. Among the reasons which contributed to the constitution of this scenario are: The legal security, the increase of the credit offered, the insertion of the largest civil construction companies in the market stock, the Minha casa Minha Vida Program (PMCMV). (MELAZZO, 2013). Launched in 2009 the PMCMV came as a response to the global economic crisis, which exploded in the United States in 2008. This program stands out for its wide territorial reaching thousands of counties, and for its great impact on political, economic, and social instances. After all, since the extinction of the National Housing Bank (BNH), which acted between the decades from 1960 to 1980, the State did not invest in the housing segment in such a strong way. In this context, this research aims to analyze the real estate production of the “Minha Casa Minha Vida” Program in Crato, Juazeiro do Norte and Barbalha cities in Ceará state. The theoretical contribution of the research is structured in two main thematic axes: Urban insertion and socio-spatial segregation. As methodological procedures should be mentioned: (1) methodological matrix construction; (2) conducting fieldwork and interviews; (3) documentary analysis; (4) database organization; (5) cartograms production. The spatial clipping choice comes from the fact that the cities of Crato, Juazeiro do Norte and Barbalha, which form the popular triangle CRAJUBAR, represent an important part of Ceará South region, as they shelter health and education equipment, in addition to concentrating economic activities such as trade, services, industry and tourism, supplying some necessities from surrounding counties, including other states, such as Pernambuco, Piauí and Paraíba. The cities in question have their urban growth even more integrated in this last decade due to the expansion of the civil construction, reflecting the national reality of effervescence from the real market estate. There is, in fact, an intimate relationship between the real production estate of CRAJUBAR and the Minha Casa, Minha Vida, leading to profound changes in the internal structuring of cities and regional urban structuring.